Understanding “Unicorn” Beyond Valuation A Study Of Marketing And Funding Strategies Of 4 Indian Start Ups (Journal of Pharmaceutical Negative Results, 2023)
It takes years to build a brand which can boast of a valuation of more than a Billion Dollar. But the business acumen of some of the entrepreneurs of today’s time have taken their respective start-ups to such heights that they could achieve what others only dream of- a Billion Dollar valuation. The story of any Unicorn is always fascinating because a Unicorn is much more than just the valuation. It is the disruptive idea, vision, strategy and the sustainable goal of the team that makes the start-up a “Unicorn”. This paper aims at gaining an insight into the marketing and funding strategies of four Indian Start-Ups viz. CRED, Meesho, BharatPe and Nykaa. The founders of these start-ups chose revenue over valuation and focused on building a brand that eventually turned into a “Unicorn”. The findings of this paper revealed some path breaking marketing and funding strategies like influencer marketing, omnichannel marketing et al.